Psychological issues of formation of socio-cultural values in students - Rashid Vakil, Jabbarov (2021)
This article is devoted to the study of psychological issues of formation of socio-cultural values in students. Schwartz personal values questionnaire, S. Shostrom's SAT methodology and the author's questionnaire were used for measurement in the research. 140 bachelors participated in the study. The aim of the research is to determine the relationship between socio-cultural values and personality traits, academic achievements, financial status and self-realization in students and to identify the values that dominate in this direction. Academic achievement, demographics, living standards and gender differences were taken as key factors. Experimental and control groups were used during the study. The analysis of the results showed that there is a positive correlation between personality traits and social cultural values, but this trend is typical. The relationship between students' self-realization values and personality traits is higher than other values. It can be concluded that these values are individual in nature and partially include socio-cultural values. (r = 0.68, r = 0.52, r = 0.64).It was found that the relationship between multicultural and altruistic values and personality traits is positive in several respects, especially initiative (r = 0.26), responsibility (r = 0.73), optimism (r = 0.43). The study showed that the correlation between students' values and academic achievement (r = 0.599 **), financial status (r = 0.564 **) and demographic factors (r = 0.446 **) is important. It can be suggested that in order to form socio-cultural values in students, it is necessary to develop personality traits, including opportunities for self-realization, to create a favorable educational environment for them.